IDENTIFICATION AND CHARACTERIZATION OF THE FOYER OF THE NATIONAL THEATER OF COSTA RICA AS PART OF THE METHODOLOGICAL STRATEGY FOR THE THREE-DIMENSIONAL MODELING OF THE FUTURE DIGITAL TWIN - I. Hernández-Salazar; J. P. Bulgarelli-Bolaños (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2023)
This paper summarizes the first results of the third specific objective of the research project: Digital Twin (DT) as a management tool for the programmed conservation plan (PCP), case study: Foyer and Smokers of the National Theater of Costa Rica (TNCR, by its Spanish acronym), developed with the support of the Vice Rectory of Research and Extension of the Technological Institute of Costa Rica. This objective aims to integrate graphic, non-graphic and linked information from the diagnostic stages of the PCP, through three-dimensional modeling, for the definition of conservation actions and future visualization of the DT. However, prior to modeling it was necessary to understand the composition of the structural system of the first body of the TNCR. The project has the information of the building systematized in documents and plans, both original and from subsequent studies and interventions, as well as a three-dimensional model made in 2021. However, there is no "as built" information after the construction or the interventions that have been carried out; in addition, the structural information of foundations, mezzanines and roofs is not integrated with the ornamental and pictorial information; that is, prior to this research there was no precise documentation of the structural elements that make up the study area and that support the heritage with artistic value of the building. Therefore, this paper presents the work carried out between June 2022 and March 2023 to identify and characterize the components of the Foyer and Smokers of the TNCR, using non-invasive techniques.